ملامح من الأدب الشعبي السوداني - د. إسماعيل موسى أبكر علي (White Nile Journal for Studies and Research, 2024)
This study aims to shed light on Sudanese folk literature, especially popular poetry, through international, Arabic and Sudanese concepts of folk literature. The study relied on dealing with samples of Sudanese poetry with its various purposes, which highlighted the poetry of Al-Dubay, Al-Masadir and Al Baramkeh poetry, and these models came from the north, east, middle and west of Sudan. The study concluded that folk poetry is abundantly available in different parts of Sudan, due to the large number of Sudanese tribes and their use of this kind of poetry, and the simplicity of the popular vocabulary gave a wonderful artistic image of Sudanese poetry